Minichannel and minigap classification criteria based on the aspect ratio of the minigeometry: A numerical study. (December 2021) - Dąbrowski, Paweł; Kumar, Ritunesh
Abstract: A detailed numerical investigation has been carried out to analyze the diabatic flow distribution and velocity profile in 18 minigeometries with various aspect ratios for V-type and I-type flow configurations (for 36 cases) assuming ethanol as a working fluid. The aim of the study is to distinguish the value of the aspect ratio for which the flow in minigeometry starts to be two-dimensional (minigap). Cases with a constant Reynolds number of 4167 (variable mass flow rate) were compared. The normalized velocity profiles over the normalized width of the minigeometry acquired from the simulation have been compared with the theoretically calculated profiles based on the one-seventh power-law and turbulent flow theory. The results show that the one-seventh power-law velocity profiles are not consistent with the profiles simulated at an aspect ratio greater than 7. A new correlation for normalized velocity profile incorporating aspect ratio of the minigeometry for minigaps has been proposed. The conclusions are independent of the geometry depth, working fluid, and flow configuration. Highlights: The minigeometries related nomenclature unification has been proposed. The normalized flow velocity profiles for various aspect ratios have been compared. The minichannel-minigap aspect ratio threshold has been distinguished. The new correlation for normalized velocity profiles in minigaps has been proposed.